2016
DOI: 10.17265/2161-6248/2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Education and Development of Pakistan: A Study of Current Situation of Education and Literacy in Pakistan

Abstract: This paper aimed to look at past educational developments in Pakistan through case study and its analysis with the present world. It primarily addressed the causes of illiteracy in Pakistan, and overcame the flaws of earlier works. Pakistani government claims that they have accomplished significantly in the educational development. Pakistani law requests government to provide free basic education system to every citizen of Pakistan. However, the enrollment rate has remained below 60%. Similarly, literacy rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 1 publication
0
22
0
Order By: Relevance
“…Such as, Sabatayeva et al (2017) discussed that the overall students were satisfied with the facilities provided in higher education. Ashraf, Muhammad Azeem, and Hafiza Iqra Ismat (2016) concluded that the outdated curriculum decreased educational quality. The teachers are the main source to transmit the quality of any program and deliver prestigious knowledge to the students.…”
Section: Discussionmentioning
confidence: 99%
“…Such as, Sabatayeva et al (2017) discussed that the overall students were satisfied with the facilities provided in higher education. Ashraf, Muhammad Azeem, and Hafiza Iqra Ismat (2016) concluded that the outdated curriculum decreased educational quality. The teachers are the main source to transmit the quality of any program and deliver prestigious knowledge to the students.…”
Section: Discussionmentioning
confidence: 99%
“…Pakistan is the sixth most populated country in the world, with 63% population under the age of 25 years and the fourth largest pool of out-of-school children (UNESCO, 2017). Most of these out-of-school children are residing in remote, rural or underprivileged city areas where prevailing challenges in providing quality education include a shortage of good teachers, the hidden child labor challenge, affordability and cultural barriers to pursuing educational goals (Titola-Meskanen, 2014;Ashraf & Ismat, 2016). Family socioeconomic status (SES), parents' education, income, and occupation all determine the level of respect in the society (Ghazi, et al, 2013).…”
Section: 2mentioning
confidence: 99%
“…However, EE consists of grade I-VIII in the country as it is mentioned in the NEP (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010), while before, the elementary education was counted from grade VI-VIII. As far as the function of the EE is concerned, it is a well-known fact that lack of attention on the quarter concerned and shortage of funds, make the primary schools of public sector non-functional and thereafter the administration of public sector schools does not utilize the given funds properly (Ashraf & Hafiza, 2016). B.Ed.…”
Section: Introductionmentioning
confidence: 99%